Quality with equity : the primary education agenda - Education Watch Project (Bangladesh); Ahmed, Manzoor, 1940-; Nath, Samir R.; Hossain, Altaf (Md. Altaf); Kabir, Mahbubul; Kalam, Abul.; Shahjamal, Mirja M.; Yasmin, Rosie Nilufar; Zafar, Tata; Campaign for Popular Education (Organization) (Dhaka : Campaign for Popular Education, Bangladesh, 2005)
In the Bangladesh context.
"Education Watch report, 2003/04."
Includes statistical tables.
Includes bibliographical references (pages [143]-145) and index.
BIED
Complimentary copy from BIED
Includes passages in Bengali.
Keywords: Education, Primary -- Bangladesh; Education, Primary -- Bangladesh -- Evaluation; Education, Primary -- Aims and objectives -- Bangladesh